2020
DOI: 10.3390/ijms21062070
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Reduces Bacterial Fouling and Promotes Fibroblasts’ Adhesion onto Chitosan 2D-Wound Dressings

Abstract: Wound healing is a dynamic process that can be seriously delayed by many factors including infectious complications. The development of dressings with intrinsic wound healing activity and/or releasing bioactive compounds may help with addressing such an issue. In this study, hyaluronic acid (HA) at different percentages (1–35%) was used to modify chitosan (CS) biological and physico-chemical properties in order to obtain 2D-matrices able to promote healing and protect from infection. HA incorporation in the CS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 47 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…However, these soft materials often suffer from poor mechanical resistance and low stability in water environment, which may compromise their in-use performance. That's also the case of chitosan, a natural polycation deriving from the partial deacetylation of chitin, largely investigated for biomedical applications, because of its outstanding biological properties including mucoadhesivity and antimicrobial properties (Amato et al, 2018;Cuzzucoli Crucitti et al, 2018;Francolini, Donelli, Crisante, Taresco, & Piozzi, 2015;Silvestro et al, 2020;Wang et al, 2020). Additionally, more than other natural polymers, chitosan triggers a minimal foreign-body response and fibrous encapsulation (Bhattarai, Edmondson, Veiseh, Matsen, & Zhang, 2005;Jayakumar, Prabaharan, Nair, & Tamura, 2010;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, these soft materials often suffer from poor mechanical resistance and low stability in water environment, which may compromise their in-use performance. That's also the case of chitosan, a natural polycation deriving from the partial deacetylation of chitin, largely investigated for biomedical applications, because of its outstanding biological properties including mucoadhesivity and antimicrobial properties (Amato et al, 2018;Cuzzucoli Crucitti et al, 2018;Francolini, Donelli, Crisante, Taresco, & Piozzi, 2015;Silvestro et al, 2020;Wang et al, 2020). Additionally, more than other natural polymers, chitosan triggers a minimal foreign-body response and fibrous encapsulation (Bhattarai, Edmondson, Veiseh, Matsen, & Zhang, 2005;Jayakumar, Prabaharan, Nair, & Tamura, 2010;Kim et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Among polysaccharides, chitosan (CS) is the most employed thanks to its similarity to naturally occurring glycosaminoglycan and its excellent properties like biocompatibility, biodegradability, non-toxicity, and easy processability. Recently, CS combined with nanoparticles, fibres or blended with other polymers has achieved a predominant role as a candidate for biomedical applications [9][10][11]. CS is a linear copolymer composed of D-glucosamine and N-acetyl-D-glucosamine units connected by (1)(2)(3)(4) glyosidic bonds obtained by N-deacetylation of chitin.…”
Section: Introductionmentioning
confidence: 99%
“…The materials used include the antioxidants polyurethane, collagen, bacterial cellulose, CS, silica gel, HA, alginate, etc. [141][142][143][144][145][146][147][148] In recent years, studies have found that lasers and tissue-engineered alternatives can shorten the healing time of leg ulcers, pressure ulcers, diabetes, and wounds at high risk of infection. 15 Compared with traditional treatment methods, modern treatment methods have solved the problems of dosage, safety, formulation, cost, production method, batch, and efficacy to a certain extent.…”
Section: Treatment Strategies For Bacterially Infected Wounds Traditi...mentioning
confidence: 99%